ТАЪЛИМ ТИЗИМИДА ВА ИЖТИМОИЙ ҲАЁТДА ҲАДИСЛАРДАН ФОЙДАЛАНИШНИНГ ПСИХОЛОГИК-ПЕДАГОГИК АҲАМИЯТИ - Қодирова, А.Б. (SCIENCE and SOCIETY, 2023)
The article analyzes the psychological and pedagogical importance of using Hadiths in the educational system and social life. Also, the role of the Holy Qur'an and Hadiths as the main sources in the spiritual and moral upbringing of a perfect generation was discussed.
Keywords: educational system; social life; moral values; mature generation; Hadis